Effect of icing roughness on wind turbine power production. Issue 4 (20th September 2016) - Blasco, Peter; Palacios, Jose; Schmitz, Sven
Abstract: The objective of this work is a quantitative analysis of power loss of a representative 1.5‐MW wind turbine subject to various icing conditions. Aerodynamic performance data are measured using a combination of ice accretion experiments and wind tunnel tests. Atmospheric icing conditions varying in static temperature, droplet diameter and liquid water content are generated in an icing facility to simulate a 45‐min icing event on a DU 93‐W‐210 airfoil at flow conditions pertinent to 80% blade span on a 1.5‐MW wind turbine. Iced airfoil shapes are molded for preservation and casted for subsequent wind tunnel testing. In general, ice shapes are similar in 2D profile, but vary in 3D surface roughness elements and in the ice impingement length. Both roughness heights and roughness impingement zones are measured. A 16% loss of airfoil lift at operational angle of attack is observed for freezing fog conditions. Airfoil drag increases by 190% at temperatures near 0° C, 145% near 10° C and 80% near 20° C. For a freezing drizzle icing condition, lift loss and drag rise are more severe at 25% and 220%, respectively. An analysis of the wind turbine aerodynamic loads in Region II leads to power losses ranging from 16% to 22% for freezing fog conditions and 26% for a freezing drizzle condition. Differences in power loss between icing conditions are correlated to variance in temperature, ice surface roughness and ice impingement length. Some potential control strategies are discussed for wind turbine operators attempting to minimize revenue loss in cold‐climate regions. Copyright © 2016 John Wiley & Sons, Ltd.